Converting textile waste into value-added chemicals: An integrated bio-refinery process - Eun Jin Cho; Yoon Gyo Lee; Younho Song; Ha Yeon Kim; Dinh-Truong Nguyen; Hyeun-Jong Bae (Environmental Science and Ecotechnology, 2023)
The rate of textile waste generation worldwide has increased dramatically due to a rise in clothing consumption and production. Here, conversion of cotton-based, colored cotton-based, and blended cotton-polyethylene terephthalate (PET) textile waste materials into value-added chemicals (bioethanol, sorbitol, lactic acid, terephthalic acid (TPA), and ethylene glycol (EG)) via enzymatic hydrolysis and fermentation was investigated. In order to enhance the efficiency of enzymatic saccharification, effective pretreatment methods for each type of textile waste were developed, respectively. A high glucose yield of 99.1% was obtained from white cotton-based textile waste after NaOH pretreatment. Furthermore, the digestibility of the cellulose in colored cotton-based textile wastes was increased 1.38–1.75 times because of the removal of dye materials by HPAC-NaOH pretreatment. The blended cotton−PET samples showed good hydrolysis efficiency following PET removal via NaOH–ethanol pretreatment, with a glucose yield of 92.49%. The sugar content produced via enzymatic hydrolysis was then converted into key platform chemicals (bioethanol, sorbitol, and lactic acid) via fermentation or hydrogenation. The maximum ethanol yield was achieved with the white T-shirt sample (537 mL/kg substrate), which was 3.2, 2.1, and 2.6 times higher than those obtained with rice straw, pine wood, and oak wood, respectively. Glucose was selectively converted into sorbitol and LA at a yield of 70% and 83.67%, respectively. TPA and EG were produced from blended cotton−PET via NaOH–ethanol pretreatment. The integrated biorefinery process proposed here demonstrates significant potential for valorization of textile waste.